2017
DOI: 10.1159/000484531
|View full text |Cite
|
Sign up to set email alerts
|

Impact of an in-Hospital Patient Education Program on Choice of Renal Replacement Modality in Unplanned Dialysis Initiation

Abstract: Background/Aims: Up to 50% patients requiring dialysis receive an urgent, unplanned start (UPS) to renal replacement therapy (RRT). Most of these are initiated with an intravenous catheter and commenced and maintained on hemodialysis (HD). Although peritoneal dialysis (PD) could be an equipotent initial modality for RRT, it is used less frequently as long-term RRT in UPS patients. This multicenter-study aimed to evaluate the impact of a structured, in-hospital education program and factors influencing PD rates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 39 publications
2
18
0
1
Order By: Relevance
“…Eligible studies included incident chronic dialysis patients (n = 42) 2-4,6,8,9,13-48 and patients with CKD known to nephrology (n = 6). 5,49-53 Study designs included retrospective cohort studies (n = 27), 2,3,5,6,14-16,19-24,26,28,31-36,38,47…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eligible studies included incident chronic dialysis patients (n = 42) 2-4,6,8,9,13-48 and patients with CKD known to nephrology (n = 6). 5,49-53 Study designs included retrospective cohort studies (n = 27), 2,3,5,6,14-16,19-24,26,28,31-36,38,47…”
Section: Resultsmentioning
confidence: 99%
“…13 No randomized control trials were found in the search. The majority of studies were conducted in Europe (n = 26; 22 unique cohorts) 2,8,9,15-19,22-25,29,30,33,36,40-43,45-48,50,51 ; 11 studies were conducted in North America 3-6,14,21,26,28,31,52,53 (Canada, n = 9; 8 unique cohorts). Study cohort sizes ranged from 43 to 45 785 persons.…”
Section: Resultsmentioning
confidence: 99%
“…Patient education has been shown to help significantly improve KRT outcomes. A structured, patientcentered education program significantly increased the frequency of opting for PD in patients needing unplanned KRT in Germany [14]. A retrospective analysis conducted in South Korea, using propensity score matching, showed that patients who received multidisciplinary pre-dialysis education, compared with those who did not, commenced dialysis at a higher GFR and had less need for urgent unplanned dialysis [15].…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, expedited dialysis modality education should be provided and, if possible, family members should be involved in the decision-making process. Providing dialysis education considerably increases the use of PD, even in unplanned dialysis initiation [2,29]. In a retrospective study, patients starting urgent home-dialysis increased from 13% to 35% after implantation of in-hospital education program [2].…”
Section: Dialysis Modality Educationmentioning
confidence: 99%